PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEMUDA DAN OLAHRAGA KABUPATEN MUSI RAWAS UTARA - Muhamad Effendi (Jurnal Media Ekonomi (JURMEK), 2021)
This study examines the influence of competence and work environment on employee performance at the Department of Youth and Sports, North Musi Rawas Regency. This research method uses a questionnaire method with analysis using the SPSS 22 for windows program. The research data was obtained from the employees of the Youth and Sports Office of North Musi Rawas Regency. The results of this study indicate that: 1) Competence has a significant effect on employee performance at the Youth and Sports Office of North Musi Rawas Regency as evidenced by the t test results showing that the value = 3.169 greater than = 2.002 means rejected and accepted, 2) Partially Environmental Work has a significant effect on employee performance at the Youth and Sports Office of North Musi Rawas Regency as evidenced by the results of the t test showing that the value = 2.638 is greater than = 2.002 meaning rejected and accepted, and 3) Simultaneously Competence and work environment have a significant effect on employee performance in The Youth and Sports Office of North Musi Rawas Regency is proven by the results of the F test showing that the value = 5.374 greater than = 3.15 means that it is rejected and accepted.